Validity and reliability of concept inventory test in human physiology - Gio Jay B. Aligway; Angeli V. Collano; Eljoy P. Barroca; Anna Clarissa D. Aves; Juneflor F. Catubay; Jennifer T. Edjec; Ma. Diana A. Butaya; Sylvester T. Cortes; Jo C. Delos Angeles (University of Muhammadiyah Malang, 2024)
Biology education plays a vital role in nurturing the understanding of learners about the intricacy of life. Various efforts have emerged to strengthen learning biological concepts but there were still studies that showed that learners have low mastery in some aspects. To determine how well students understood various biological topics, including human physiology, Concept inventory tests (CIT) were used. The concept inventory test may be able to spot students' misconceptions and ultimately lead to improved comprehension. The crafted CIT developed with the aid of a table of specifications based on Bloom’s taxonomy of cognitive domain was assessed according to its validity and reliability. In validation, content validity and item analysis were considered while reliability test was employed through Cronbach’s alpha. Distractor analysis was also performed to determine possible source of misconception per item. The CIT was administered to 120 senior high school STEM students (50.8% from the private schools, 37.5% in regular public schools and 11.7% from public schools with special programs in science). The results displayed high content validity with a mean of 4.83 for content validity and an average Aiken’s validity coefficient of 0.98. It also highlighted that the test is moderately difficult with the test difficulty of 0.58, as well as, discriminatory with a discriminating level of 0.46. After item classification, 63 items were retained (39 accepted, 24 for revisions) and Chronbach’s alpha (α=0.74) indicated good internal consistency. The concept inventory test propounds to be a good classroom test with minor items to be revised.